PROBLEMS OF THE FORMATION OF INTERCULTURAL TEACHERS: FORMATIVE STRATEGIES FOR A MULTICULTURAL SOCIETY - Moraes Armesto, Leonardo; Paiva Gonçalves Bispo, Patrícia; Roberto Alonso, Thabata (Revista Gênero e Interdisciplinaridade, 2023)
The formation of teachers for multiculturalism reflects the construction and constant deconstruction of this professional, who begins his career based on his knowledge and experiences. When he or she becomes an educator, they will go through a process of discovery where reflection and latency of innovation in their activities are necessary throughout their career. Therefore, the complexity of today’s world and the great changes in the media (and its contents) have transformed the ways of educating, making this task even more arduous and with an even greater weight of social responsibility. It is necessary to raise the teacher’s awareness in order to provide a situation of construction of valid knowledge and to generate an interactive and dialectical attitude, so that he or she realizes the permanent need for updating, in face of the changes that are taking place. It will no longer be possible to organize teaching around rigid lessons and reproductive classes. It will be necessary to permanently elaborate didactic learning conditions and situations that better meet the needs of the diversity of students. This proposal is vented and awaits from the current world the dynamics of the learner in a lively, fluid and permanently attentive interface.